The Role of Potassium in Plants under Drought Stress: Mini Review - Muhammad Umair Hassan; Muhammad Aamer; Muhammad Umer Chattha; Muhammad Aman Ullah; Saira Sulaman; Muhammad Nawaz; Wang Zhiqiang; Ma Yanqin; Huang Guoqin (Journal of Basic & Applied Sciences, 2017)
Drought stress is a major catastrophe to plant productivity. Drought stress significantly reduces the crop yield and quality, and probably exceeds losses from all other stresses. Potassium (K+) is an essential nutrient and affects the growth and development, and it also contribute significantly towards plants survival under drought stress. In this mini review we discussed the physiological, biochemical, and molecular mechanisms underlying K induced alleviation of drought stress.